PENERAPAN TERAPI MUROTAL SURAH AR-RAHMAN TERHADAP KECEMASAN PASIEN CKD YANG MENJALANI HEMODIALISA - Nimas Citra Nur Baety; Ani Syafriati; Yuasti Ningsih (Jurnal Kesehatan dan Pembangunan, 2026)
Patients with Chronic Kidney Disease (CKD) undergoing hemodialysis often experience anxiety due to physical, psychological, and social changes. One non-pharmacological intervention to reduce anxiety is the recitation therapy of the Holy Qur’an (murotal), particularly Surah Ar-Rahman, which provides a calming effect through spiritual stimulation and relaxation. This study aimed to determine the effect of murotal Surah Ar-Rahman therapy on anxiety levels among CKD patients undergoing hemodialysis in the Lavender Room of RSUD Ir. Soekarno, Sukoharjo Regency. The study employed a case study approach involving four patients, with anxiety levels measured using the Depression Anxiety Stress Scale (DASS-42) before and after the intervention. The murotal therapy was played for approximately 15 minutes prior to the hemodialysis procedure. The results showed a decrease in anxiety scores from the moderate to the mild category, with an average reduction from 11.5 to 7. Additionally, depression and stress scores also decreased, accompanied by more stable blood pressure following the intervention. In conclusion, the murotal therapy of Surah Ar-Rahman effectively reduced anxiety levels among CKD patients undergoing hemodialysis. This intervention can serve as a complementary spiritual nursing therapy to enhance patients’ comfort and well-being.